2013
DOI: 10.1097/pcc.0b013e3182712799
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Overload in Infants Following Congenital Heart Surgery

Abstract: Objective To describe post-operative fluid overload patterns and correlate degree of fluid overload with intensive care morbidity and mortality in infants undergoing congenital heart surgery. Design Prospective, observational study. Fluid overload (%) was calculated by two methods: 1. (Total fluid In – Total fluid Out)/(Pre-op weight) x 100; and 2. (Current weight – Pre-op weight)/(Pre-op weight) x 100. Composite poor outcome included: need for renal replacement therapy, upper quartile time to extubation or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
131
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(142 citation statements)
references
References 25 publications
(27 reference statements)
8
131
0
3
Order By: Relevance
“…It is feasible that avoidance of aggressive fluid resuscitation and subsequent fluid overload in the immediate postoperative period could lead to better outcomes including decreased PLOS, especially in patients with other risk factors for persistent pleural drainage. Of note, positive fluid balance was on average near ten times greater in patients with both PCTO and PLOS, which is consistent with findings of the deleterious effects of volume overload in other pediatric cardiac surgical populations [13].…”
Section: Discussionsupporting
confidence: 86%
“…It is feasible that avoidance of aggressive fluid resuscitation and subsequent fluid overload in the immediate postoperative period could lead to better outcomes including decreased PLOS, especially in patients with other risk factors for persistent pleural drainage. Of note, positive fluid balance was on average near ten times greater in patients with both PCTO and PLOS, which is consistent with findings of the deleterious effects of volume overload in other pediatric cardiac surgical populations [13].…”
Section: Discussionsupporting
confidence: 86%
“…Mean filter life was 51.1 h. Similar to other studies in pediatric CRRT patients [2][3][4]5], fluid overload (FO), defined by the percentage weight gain over weight at admission to the neonatal intensive care unit (NICU), was independently associated with mortality [6]. Neonatal studies have reported an FO of >15-20 % to be associated with poor outcome defined as need for CRRT, prolonged NICU stay, time to extubation or death within 30 days postcardiothoracic surgery [7,8]. Interestingly, this study by Lee and Cho [1] reports a much higher FO cut-off of 30 % being associated with poor outcomes, including 100 % mortality for patients reaching an FO of >30 %.…”
supporting
confidence: 53%
“…Traditional teaching has emphasized the need for fluid resuscitation aiming to maintain renal perfusion and maintain urine output in patients with or at risk of AKI. However, the clinical literature has consistently demonstrated the fluid overload is particularly harmful in AKI; in a previous review, 38 the authors identified 17 observational studies examining fluid balance and outcomes in patients with AKI from 2008 to 13,8,9,11,14,[39][40][41][42][43][44][45][46][47][48][49][50] and all demonstrated evidence of harm from fluid overload and/or benefit from its resolution. Prospective evidence supporting improved renal outcome with active avoidance of fluid overload is also available from the FACTT study whereby conservative fluid management was associated with a strong trend toward a lower need for renal replacement therapy 6 and a lower incidence of AKI in a post hoc analysis adjusted for fluid balance.…”
mentioning
confidence: 99%